Phenolic Compounds and Antioxidant Properties of Grape Berries and Wines in Loess Plateau Region (China) - Jiang, Bao; Zhang, Zhen-Wen (Asian Journal of Chemistry, 2011)
Four grape samples (Cabernet Sauvignon1, Cabernet Sauvignon2, Cabernet Gernischet and Chardonnay) and corresponding wines, produced from Loess Plateau region of China, were examined in present studies. The antioxidant activity of grape berries and wines was measured by different analytical methods (DPPH, CUPRAC, SRSA and FTC) and the contents of total phenols, total flavonoids, total flavanols and total anthocyanins were determined. As expected, the red grape berries and corresponding wines had much higher phenolic content and antioxidant capacity than the white grape berries and corresponding wine, respectively. Furthermore, the results also indicated that ecological factor of vineyard strongly influenced the contents of the phenolic compounds and antioxidant capacity in grape berries and wines. Finally, the correlation between the phenolic contents and the antioxidant capacity as well as 9 individual phenolic compounds contents and antioxidant capacity of grape berries and wines has been investigated. The analyses show that the former correlation is close and the latter correlation exists discrepant. The fact is concluded that the grape berry and wine's antioxidant properties are influenced differently by each polyphenolic molecule.